AI-driven approaches for optimizing power consumption: a comprehensive survey - Parag Biswas; Abdur Rashid; Angona Biswas; Md Abdullah Al Nasim; Sovon Chakraborty; Kishor Datta Gupta; Roy George (Discover Artificial Intelligence)
Abstract Reduced environmental impacts, lower operating costs, and a stable, sustainable energy supply for current and future generations are the main reasons why power optimization is important. Power optimization ensures that energy is used more efficiently, reducing waste and optimizing the utilization of resources. In today’s world, the integration of power optimization and artificial intelligence (AI) is essential for transforming how energy is produced, used, and distributed. AI-driven algorithms and predictive analytics enable real-time monitoring and analysis of power usage trends, allowing for dynamic adjustments to effectively meet demand. Efficiency and sustainability are enhanced across various sectors by optimizing power consumption through intelligent systems. This survey paper provides an extensive review of the different AI techniques used for power optimization, along with a systematic analysis of the literature on the application of intelligent systems across diverse areas of power consumption. The literature review evaluates the performance and outcomes of 17 distinct research methodologies, highlighting their strengths and limitations. Additionally, this article outlines future directions for the integration of AI in power consumption optimization.